THE RELATIONSHIP BETWEEN GADGET USE AND DIGITAL LITERACY IN BIOLOGY EDUCATION STUDENTS OF HKBP NOMMENSEN UNIVERSITY - Sirait, Gloria; Wardany, Nur; Purba, Melfa Uli Magdalena (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
Abstract: Technology and information have progressed quite rapidly, as seen from the emergence of gadgets as a means of communication. Given the importance of digital literacy in responding to what is obtained from the internet, the author wants to see how the relationship between the use of gadgets and digital literacy in biology education students at HKBP Nommensen University Pematangsiantar. The sample was taken by the purposive sampling method with students majoring in biology education at HKBP Nommensen Pematangsiantar university as a sample. The purpose of this study is to analyze the relationship between the use of technology and digital literacy in biology students HKBP Nommensen University Pematang Siantar which often utilizes technology. The research method uses qualitative research methods and saturated sampling strategies. Google Form surveys with Likert scale are used to collect data. Judging from the survey, Generation Z is currently more dominant in watching videos than literate through e-books with a percentage rate of 78.4%. The low digital literacy among Generation Z is influenced by the wrong use of gadgets. There is a close relationship between digital literacy and the use of gadgets, namely using gadgets to find existing sources to increase one's insight and ability to improve quality in oneself. Keywords: gadgets; digital literacy, biology students, HKBP Nommensen University Pematang Siantar Abstrak: Teknologi dan informasi mengalami kemajuan yang cukup pesat, terlihat dari munculnya gadget sebagai alat komunikasi. Mengingat pentingnya literasi digital dalam menyikapi apa yang di dapat dari internet maka penulis ingin melihat bagaimana hubungan penggunaan gadget dengan literasi digital pada mahasiswa pendidikan biologi di Universitas HKBP Nommensen Pematangsiantar. Sampel diambil dengan metode purposive sampling dengan mahasiswa jurusan pendidikan biologi di universitas HKBP Nommensen Pematangsiantar sebagai sampel. Tujuan penelitian ini adalah untuk menganalisis hubungan antara penggunaan teknologi dan literasi digital pada Mahasiswa Universitas HKBP Nommensen Pematangsiantar yang sering memanfaatkan teknologi. Adapun metode penelitian ini menggunakan metode penelitian kualitatif dan strategi sampling jenuh. Survei Google Form dengan skala Likert digunakan untuk mengumpulkan data. Dilihat dari survei tersebut bahwa generasi Z saat ini lebih dominan senang melihat video daripada berliterasi melalui e-book dengan tingkat presentase 78,4%. Rendahnya literasi digital di kalangan generasi Z dipengaruhi oleh penggunanan gadget yang salah. Terdapat hubungan yang erat antara literasi digital dengan penggunaan gadget yaitu menggunakan gadget untuk mencari sumber -sumber yang ada untuk meningkatkan wawasan serta kemampuan seseorang guna meningkatkan kualitas dalam dirinya. Kata kunci: gadget; literasi digital; mahasiswa pendidikan biologi, Universitas HKBP Nommensen